UJI TOKSISITAS EKSTRAK ETANOL BATANG KAYU WOLE WOE TERHADAP LARVA Artemia salina Leach MENGGUNAKAN METODE Brine Shrimp Lethality Test (BSLT) - Virsa Handayani; Safriani Rahman; Andi Nur Alam Amaliah (Fakultas Farmasi UMI, 2022)
The Wole Woe plant is one of the plants that is empirically used as traditional medicine by the Weda community in Central Halmahera Regency. The stem part of the Wole Woe plant is used to treat various diseases. This study aims to determine the toxicity of Wole Woe logs using the Brine Shrimp Lethality Test (BSLT) method. This research was started by extracting Wole Woe logs using ethanol 70% solvent with the reflux method and then carried out phytochemical screening which showed that Wole Woe logs contained alkaloids, flavonoids, saponins, triterpenoids, and tannins compounds. Toxicity testing of Wole Woe wood stem ethanol extract against Artemia salina Leach larvae was divided into 5 test groups, namely 4 treatment groups (concentrations of 250 ppm, 500 ppm, 750 ppm, and 1000 ppm) and 1 control or comparison group (sea water). Each concentration was made in 3 vials containing 10 larvae of Artemia salina Leach. Observations were made by looking at the mortality of Artemia salina Leach larvae after 24 hours of treatment. The results of the study can be seen through probit analysis by calculating the LC50 value. The LC50 of the ethanol extract of Wole Woe logs is 453.942 ± 59.564 g/mL. This indicated that the ethanolic extract of Wole Woe logs had a toxic effect on Artemia salina Leach larvae because the LC50 value was< 1000 ppm